PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KARYAWAN SEBAGAI VARIABEL INTERVENING DI PT EKOS JAYA ABADI LESTARI KABUPATEN SIDOARJO - Agung Dwi Nugroho (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2019)
This research was conducted to determine the influence of leadership and work environment on the performance of employees who through the employee satisfaction as a intervening variable. The purpose of the study is to know the direct influence between each variable, and the indirect influence between the leadership variables and the working environment towards the employee's performance through the satisfaction of designed as intervening variables. This research is done using a quantitative approach. Research that focuses on hypothesis testing with statistical method analysis tools and generates conclusions. The population of this research is the consumer of PT Ekos Jaya Abadi Lestari District Sidoarjo with samples of 50 respondents using the formula Slovin. Methods of collecting documentation data and questionnaires. While data analysis is done through path analysis to figure out the direct influence using SPSS 25.0 for Windows and for indirect effect using the Sobel test method. Based on the analysis of the lines known that the direct influence of the leadership variables have a coefficient value of 0.624 with a value of statistic 2.785 to employee satisfaction, the working environment variable has a coefficient value of 0.352 With the value of statistic 2.569 to employee satisfaction, the leadership variable has a coefficient value of 0.639 with 3.300 value statistic to employee performance, the working environment variable has a coefficient value of 0.688 with the value of Statistic 3.740 to employee performance, employee satisfaction variables have a coefficient value of 0.443 with 3.800 value statistic against employee performance, and indirect influence of leadership variables against employees ' performance Employee satisfaction has a coefficient value resulting from a Sobel test of 0.276 with a value of statistic 3.285, a working environment variable to performance through employee satisfaction has a coefficient value of 0.155 with a value of statistic 2.152. Based on these results it can be seen that the indirect influence of the working environment variables on employee performance through the employee satisfaction is at least the dominance compared to the influence among other variables.